posted by brianna on .
Let g(x) = 0.5x + 18. Write the rule for g-1(x). Then, evaluate g-1(x) at x = 20. Enter this result in the space provided.
Your umpteen posts have been removed.
To quote one of our very good math and science tutors: “You will find here at Jiskha that long series of questions, posted with no evidence of effort or thought by the person posting, will not be answered. We will gladly respond to your future questions in which your thoughts are included.”
Let y = g(x) = 0.5x + 18
0.5x = (y-18)
x = 2y -36.
Switch x and y for the inverse function, and x becomes the inverse function g^-1(x)
g^-1(x) = 2x - 36
g^-1(20) = 4